Risk factors associated with isoniazid resistance in tuberculosis - Barnard, Marinus (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MScMed (Biomedical Sciences. Molecular Biology and Human Genetics))--University of Stellenbosch, 2005.